Keanekaragaman Nepenthes Pada Kawasan Kebun Bonsai dan Sekitarnya di Cagar Alam Dolok Sibual Buali, Sumatera Utara - Novha Nurul Fadillah; Pindi Patana; Yunasfi Yunasfi (Peronema Forestry Science Journal, 2014)
Nepenthes is one of the few carnivorous plants which popular as ornamental plant. Sumatran has the richest Nepenthes flora after Borneo, with 29 species. This research was done in Dolok Sibual Buali Nature Reserve at May until June 2013. The purpose of this research is to identify the types of Nepenthes and to know the dominance type of Nepenthes in Dolok Sibual Buali Nature Reserve. Research location determined by using cluster method at three different location, there is 1200 m a.s.l., 1400 m a.s.l., and 1500 m a.s.l. Area size of observation was 0.6 Ha with 15 plots. The result of this research showed that 6 species Nepenthes founded in this area, the species are N. bongso, N. ovata, N. reinwardtiana, N. rhombicaulis, N. sumatrana, and N. tobaica. N. reinwardtiana was the largest species that discover with 152 clumps/0.6 Ha (32.55%) and the lowest species was N. sumatrana with 22 clumps/0.6 Ha (4.71%). The highest index diversity of the Nepenthes spp. was discovered in location III (1500 m a.s.l.) with 1.59.Keywords : Dolok Sibual Buali Nature Reserve, Kebun Bonsai, Biodiversity, Nepenthes